The wasp genus Clystopsenella in Early Miocene amber from the Dominican Republic (Hymenoptera: Scolebythidae) - Engel, Michael S. (Novitates Paleoentomologicae, 2015)
A new species of scolebythine wasp (Chrysidoidea: Scolebythidae) is described and figured from a female beautifully preserved in Early Miocene amber from the Dominican Republic.  The specimen is the first fossil record of the extant genus Clystopsenella Kieffer, and is quite similar to the extant Clystopsenella longiventris Kieffer, a species that occurs widely from Brazil to Belize.  Clystopsenella mirabilis Engel, new species, is distinguished from C. longiventris on the basis of size; head, pronotal, and pterostigmal shape; and putative color differences.  The living and fossil diversity of the family is summarized and evolutionary patterns within the clade are discussed.